Large extent of mercury stable isotope fractionation in contaminated stream sediments induced by changes of mercury binding forms - Schwab, Lorenz; Rothe, Florian M.; McLagan, David S.; Alten, Alexandra; Kraemer, Stephan M.; Biester, Harald; Wiederhold, Jan G. (Frontiers in Environmental Chemistry, 2022)
Mercury (Hg) release from contaminated legacy sites is a large contributor to riverine ecosystems and can represent a significant local and regional environmental issue even long after the initial site contamination. Understanding processes of in-stream species transformation is therefore important to assess the fate and bioavailability of the released Hg. In this study, we investigated in-stream Hg transformation processes with analyses of Hg binding forms and Hg stable isotopes. Stream sediments were collected downstream of a former kyanization facility (Black Forest, SW Germany), where highly soluble Hg(II)-chloride (HgCl2) was used as an anti-fouling agent to treat timber. Exfiltration of partly anoxic, contaminated groundwater with Hg concentrations of up to 700 μg/L into the adjacent Gutach stream is the main source of Hg to sediments. Total Hg concentrations in the stream bottom sediments (<2 mm) ranged from background values of 6.3 µg/kg upstream of the contaminated site to 77 mg/kg near the location of exfiltration of contaminated groundwater. A five-step sequential extraction procedure and Hg pyrolytic thermal desorption (PTD) analyses indicated changes in Hg binding forms in the sediments along the flow path towards a higher proportion of organically bound Hg. A large shift towards negative δ202Hg values was observed downstream of the contaminated site (change of ≈ 2 ‰) along with a minor offset in mass-independent fractionation. Binary mixing models based on Hg isotope ratios using one industrial and different natural background endmembers were tested to estimate their respective contribution of Hg to the sediments but failed to produce plausible allocations. Based on the observed changes in isotopic composition, total Hg concentrations and Hg binding forms, we propose that the large extent of fractionation observed in downstream sediments is the result of a combination of kinetic isotope effects during sorption, redistribution of Hg within the sediment and the preferential transport of Hg associated with the sediment fine fraction. These results highlight the importance of transformation processes when assessing the sources and fate of Hg in environmental systems and show limitations of using simple mixing models based on Hg stable isotopes.